Drilling fossils and reconstructing genomes: paleogenomics uncovers domestication, dispersal and admixture in Bos taurus - Diquelou, Deborah Yvonne (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2026)
Animal domestication is a key event in human history, yet remains complex and species-specific. This thesis investigates cattle domestication through the extraction and sequencing of 109 new ancient genomes dating from the Neolithic to the Middle Ages, analysed alongside previously generated data using mitochondrial and nuclear population genetics approaches. Results reveal the population structure of domesticated cattle across Europe and the Middle East. Mitochondrial and nuclear analyses identify admixture with indicine cattle and with local and distant wild aurochs populations. The timing and distribution of haplogroup T1 support its origin in the Middle East, followed by its later spread and predominance in Africa. These patterns of admixture and population change reflect cattle movement and management strategies closely linked to human migrations.
APPROVED
Keywords: paleogenomics; ancient DNA; Bos taurus; domestication; admixture; population genetics; mitochondrial DNA; phylogeny